Comparison of the In Vivo Distribution of Four Different Annexin A5 Adducts in Rhesus Monkeys. (4th May 2011) - McQuade, Paul; Belanger, Marie-Jose; Meng, Xiangjun; Guenther, Ilonka; Krause, Stephen; Gonzalez Trotter, Dinko; Reutelingsperger, Chris; Hostetler, Eric; Klimas, Michael; Mehmet, Huseyin; Cook, Jacquelynn
Abstract : Annexin A5 has been used for the detection of apoptotic cells, due to its ability to bind to phosphatidylserine (PS). Four different labeled Annexin A5 adducts were evaluated in rhesus monkey, with radiolabeling achieved via 1, 4, 7, 10-tetraazacyclododecane-1, 4, 7, 10-tetraacetic acid (DOTA). Of these adducts differing conjugation methods were employed which resulted in nonspecific radiolabeling (AxA5-I ), or site-specific radiolabeling (AxA5-II ). A nonbinding variant of Annexin A5 was also evaluated (AxA5-IINBV ), conjugation here was site specific. The fourth adduct examined had both specific and nonspecific conjugation techniques employed (AxA5-IImDOTA ). Blood clearance for each adduct was comparable, while appreciable uptake was observed in kidney, liver, and spleen. Significant differences in uptake of AxA5-I and AxA5-II were observed, as well as between AxA5-II and AxA5-IINBV . No difference between AxA5-II and AxA5-IImDOTA was observed, suggesting that conjugating DOTA nonspecifically did not affect the in vivo biodistribution of Annexin A5.